Measuring ESG effects in systematic investing - Ben Dor, Arik (Hoboken, NJ : John Wiley & Sons, Inc., 2024)
"Integrating ESG in Systematic Investing is unique in two respects. Firstly, given that ESG scores and policies are relevant at firm level, the book looks at integrating ESG in both equity and credit markets. Secondly, the book examines ESG through a fully quantitative and systematic lens, as opposed to existing ESG-related research, which tends to be mostly fundamental in nature. The book begins by setting out methods for measuring the ESG-specific risk premium, and moves on to cover ESG considerations in portfolio construction, the performance implications of companies' ESG Policies and the investment implications of a lack of uniformity in ESG Definitions."--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 24, 2024).
Added to collection customer.56279.3
Keywords: Impact investing; Investments -- Moral and ethical aspects; Investissements à retombées sociales; Investissements -- Aspect moral; Impact investing; Investments -- Moral and ethical aspects